3D printed wearable sensor with smart machine vision intelligence - Yu, Chew Muang (Nanyang Technological University, 2024)
Technological advancement enabled the creation of wearable devices and mobile applications to collect health data such as heart rate, body temperature and sleep patterns using various embedded sensors. Smartwatches and fitness trackers are becoming more popular nowadays because of the health tracking function. Aside from lifestyle purposes, there are also more wearable devices and mobile applications being developed for healthcare usages. Mobile applications with machine vision intelligence are able to provide more detailed analysis of medical test results. Furthermore, the continuous tracking of an individual’s health using wearable devices and mobile applications is a convenient way to keep one informed of their health. Medical professionals can also gain deeper insights to their patients’ health condition and create better treatment plans.